2005
DOI: 10.1002/jms.755
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cysteine with Cu2+ and group IIb (Zn2+, Cd2+, Hg2+) metal cations: a theoretical study

Abstract: The structure and energetics of complexes obtained upon interaction between cysteine and Zn2+, Cd2+, Hg2+ and Cu2+ cations were studied using quantum chemical density functional theory calculations with the 6-311++G** orbital basis set and relativistic pseudopotentials for the cations. Different coordination sites for metal ions on several cysteine conformers were considered. In their lowest energy complexes with the amino acid, the Zn2+ and Cd2+ cations appear to be three-coordinated to carbonyl oxygen, nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 62 publications
12
88
0
Order By: Relevance
“…PHE14 was also quite stable in the presence of multiple organic solvents, surfactants and metal ions, thus making it a very good esterase candidate for organic synthesis that requires an organic solvent, surfactant or metal ion. Similar behavior was observed with other microbial esterases [18][19][20][21]. PHE14 was also characterized to be a salt-tolerant microbial esterase.…”
Section: Discussionsupporting
confidence: 73%
“…PHE14 was also quite stable in the presence of multiple organic solvents, surfactants and metal ions, thus making it a very good esterase candidate for organic synthesis that requires an organic solvent, surfactant or metal ion. Similar behavior was observed with other microbial esterases [18][19][20][21]. PHE14 was also characterized to be a salt-tolerant microbial esterase.…”
Section: Discussionsupporting
confidence: 73%
“…These structures are similar to the GSs found in previous work for H + (Cys), 39 M + (Cys) where M = Li and Na, 20 as well as predictions by Russo et al of M 2+ (Cys) where M = Cu, Zn, Cd and Hg. 8 Previous theoretical work in the Armentrout group has found that the CS structures The IRMPD action spectra shown correspond to the fractional yield of the product ions as a function of free electron laser wavenumber.…”
Section: Theoretical Resultsmentioning
confidence: 94%
“…Nevertheless, it is difficult to explain the structures of the complexes at the atomic and electronic level. Computational studies can fill this gap and provide thermochemical, kinetic and structural information [33]. Furthermore, the different affinities of a specific ligand for different metal cations, which play a key role in the function and properties of metal-containing biomolecules, can also be obtained directly by quantum-chemical computations [34,35].…”
Section: Introductionmentioning
confidence: 99%